OVERVIEW OF VACCINATION STATUS AND COMORBIDITIES IN DEATHS DUE TO COVID-19 OMICRON VARIANT IN RIAU PROVINCE, 2022: Gambaran Status Vaksinasi dan Komorbiditas pada Pasien Meninggal Akibat COVID-19 Varian Omicron di Provinsi Riau, 2022 - Rajunitrigo, Rajunitrigo; Muryanto, Irwan; Mahkota, Renti; Siregar, Fajri Marindra; Elvita, Nina; Malfasari, Eka; Basra, Mega Utami; Marwanty, Marwanty (Universitas Airlangga, 2024)
Background: The Corona Virus Disease 2019 (COVID-19) pandemic is causing problems in public health. One of the prevention efforts is vaccination. Omicron, the new variant of COVID-19, is a variant that is spreading rapidly in Indonesia, including in Riau Province. Purpose: This study aims to describe the determinants of vaccination status in deaths of Omicron variant COVID-19 patients in Riau Province from February to April 2022. Methods: Cross-sectional research was conducted using secondary data. A total of 158 patients who died with confirmed COVID-19 and the Omicron variant via S-Gene Target Failure (SGTF) and sequencing test, and were treated at a referral hospital in Riau Province within two months (8 February – 4 April 2022) were included in the study. The distribution of patient deaths was analyzed univariately and bivariately. Results: Most of the death cases were unvaccinated (67.09%). As many as 48.73% of the 158 deaths were elderly â‰¥61 years, and the majority (70.13%) of cases were unvaccinated. It was found that 64.56% of the 158 patient deaths occurred in mainland Riau, and the majority (67.65%) were unvaccinated. Diabetes mellitus (35.86%) and cardiovascular disease (28.97%) were the highest comorbidities. Conclusion: In preventing deaths due to COVID-19, it is necessary to accelerate and increase vaccination coverage, especially for children and the elderly in land and coastal areas. Vaccination can optimize protection against COVID-19. Apart from that, efforts are needed to prevent the severity of comorbidities.